Goodbye smokers' corner: Health effects of school smoking bans - Gregor Pfeifer; Mirjam Reutter; Kristina Strohmaier (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
We estimate the causal impact of school smoking bans in Germany on the propensity and intensity of smoking. Using representative longitudinal data, we use variation in state, year, age cohort, school track, and survey time for implementation of such smoking bans to identify the effects of interest. The estimates from our multipledifferences approach show that six to ten years after intervention, propensity towards smoking is reduced by 7-16 percent, while the number of smoked cigarettes per day decreases by 8-13 percent. Our results still hold if we account for the clustered data structure by evaluating the effects with randomization inference. – – Wir untersuchen die kausalen Auswirkungen des Rauchverbots an Schulen in Deutschland auf die Wahrscheinlichkeit zu rauchen und die Anzahl gerauchter Zigaretten pro Tag. Um diese Effekte zu messen, verwenden wir einen repräsentativen Paneldatensatz und nutzen Variationen zwischen Bundesländern, Jahren, Alterskohorten, Schulformen und Interviewzeitpunkten in Bezug auf das Inkrafttreten der Intervention. Die Schätzungen unseres multiplen Differenzenansatzes zeigen, dass sich sechs bis zehn Jahre nach Einführung der Verbote an Schulen die Wahrscheinlichkeit zu rauchen um 7-17 Prozent reduziert, während die Anzahl an gerauchten Zigaretten pro Tag um 8-13 Prozent sinkt. Unsere Ergebnisse bleiben auch dann robust, wenn wir der Clusterstruktur der Daten Rechnung tragen und die Effekte mit Randomisierungsinferenz evaluieren.
Keywords: I12; I18; C12; C21; 330; school smoking ban; cigarette consumption; treatment effects; difference-in-differences; randomization inference